Isolated Rem Sleep Behavior Disorder: A Model to Assess the Overnight Habituation of Emotional Reactivity - Caterina Leitner; Viviana Greco; Francesca Casoni; Penelope A. Lewis; Luigi Ferini-Strambi; Andrea Galbiati (Clocks & Sleep)
(1) Background: Phasic events in rapid eye movement (REM) sleep are a core feature of isolated REM behavior disorder (iRBD), which is often associated with emotion dysregulation. This study explores the relationship between sleep and the overnight habituation of emotional reactivity in healthy controls (HCs) and iRBD patients, focusing on the role of REM phasic events and a specific non-REM waveform, namely sleep spindles. (2) Methods: Participants underwent polysomnography and completed arousal rating tasks and mood scales before and after sleep. In total, eight HCs (4 M, mean age 60.62 ± 6.8) and eight iRBD patients (7 M, mean age 68.25 ± 5.12) were included in the analyses. (3) Results: In HCs, longer REM sleep duration correlated positively with overnight habituation. In the whole sample, overnight habituation negatively correlated with REM sleep latency and wake-after-sleep onset, and positively with N2 sleep. Higher overnight habituation was associated with fewer REM arousals and awakenings in the whole sample, and with greater N2 sleep spindle density in HCs. (4) Conclusions: Our preliminary results suggest that REM sleep and spindles in N2 play critical roles in emotional processing. The study confirms the relationship between emotion dysregulation and REM phasic events, enhancing our understanding of how sleep impacts emotional reactivity and also in the prodromal phase of neurodegenerative disease.